Analisis Implementasi Sistem Informasi Pemerintah Daerah di Lingkungan Pemerintah Kota Bandung - Madany, Annisa Lantang; Maryani, Neni (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
The aim of this research is to understand and analyze the Implementation of the Regional Government Information System (SIPD) in Regional Apparatus of Bandung City Government, as well as the challenges and solutions for implementing SIPD in Regional Apparatus of Bandung City Government. This is a qualitative research study. The research method used in this study is descriptive research. The data validation technique used is triangulation because the data collection in this research was conducted through three (3) methods: interviews, documentation, and observation. SIPD in Bandung City has been functioning fairly well in supporting regional planning, budgeting, and financial reporting, although it still faces several challenges. From the user aspect, the system has involved relevant officials who have competencies according to their duties. However, the lack of official technical guidelines has led to non-uniform understanding of SIPD usage procedures. Data management has been systematic, but there are still information gaps in Musrenbang proposals, which hinder validation and planning. From the software perspective, the web-based SIPD provides administrative ease, but often experiences technical issues, such as login failures and document printing problems, with slow central response. Supporting infrastructure is adequate, but central server capacity often faces constraints, especially during high access periods. Additionally, internal control is not yet optimal because the Inspectorate still relies on physical documents, making real-time supervision suboptimal. To address these challenges, more comprehensive technical guidelines, improved data quality, software optimization, strengthened server infrastructure, and enhanced role of the Inspectorate in system supervision are needed.